2017
DOI: 10.25260/ea.17.27.3.0.434
|View full text |Cite
|
Sign up to set email alerts
|

Uso de la tierra y ambiente local de descomposición en el Chaco Semiárido de Córdoba, Argentina

Abstract: R������.El cambio en el uso de la tierra es un proceso clave debido a sus efectos directos sobre la identidad y la estructura de la vegetación. En el Chaco Semiárido se conoce poco acerca del impacto de los cambios en la vegetación sobre los procesos relacionados con el ciclado de nutrientes (e.g., la descomposición). En este trabajo analizamos si las modificaciones en la vegetación, producto de distintas intensidades en el uso de la tierra, producen cambios en las condiciones del ambiente local, y si estos ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(54 reference statements)
3
3
0
Order By: Relevance
“…The different quadrats where the retention experiment was carried out were characterized by different degrees of vegetation complexity, which in turn was strongly associated with land use regime: the ecosystem type with the most intense long‐term biomass removal (open shrubland) was the one showing the simplest vertical structure, lowest ground cover and a dominance of grasses and S. sellowii in the surface layer. These changes in vegetation structure and ground cover type are consistent with those reported as the consequences of long‐term intense biomass removal by grazing and logging in the semiarid Chaco (Bregaglio, Karlin, & Coirini, ; Cabido et al., , ; Coirini et al., ; Conti & Díaz, ; Conti et al., ; Cuchietti et al., ; De Casenavea, Pelottob, & Protomastro, ; Gardner et al., ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The different quadrats where the retention experiment was carried out were characterized by different degrees of vegetation complexity, which in turn was strongly associated with land use regime: the ecosystem type with the most intense long‐term biomass removal (open shrubland) was the one showing the simplest vertical structure, lowest ground cover and a dominance of grasses and S. sellowii in the surface layer. These changes in vegetation structure and ground cover type are consistent with those reported as the consequences of long‐term intense biomass removal by grazing and logging in the semiarid Chaco (Bregaglio, Karlin, & Coirini, ; Cabido et al., , ; Coirini et al., ; Conti & Díaz, ; Conti et al., ; Cuchietti et al., ; De Casenavea, Pelottob, & Protomastro, ; Gardner et al., ).…”
Section: Discussionsupporting
confidence: 85%
“…Along the transect and every 5 m, we set a 50 cm × 50 cm quadrat (10 quadrats per plot). In each quadrat, we measured the following descriptors of vegetation complexity: ground cover percentage, vertical structure (estimated by the number of vegetation touches on a marked 2‐m pole, Gardner et al., ) and ground cover types (estimated as the percentage of litter, forbs, graminoids and Selaginella sellowii , based on previous studies by Cabido et al., ; Conti et al., ; Conti & Díaz, ; Cuchietti et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our index included not only different intensities of present and past land use (represented as the different ecosystem types), but also the variation of these ecosystem types in time, through a local control. These control plots enabled us to assess the impact of different intensities of land use, confirming the general findings of previous studies (Conti & Díaz, 2013;Conti et al, 2016Conti et al, , 2018Cuchietti et al, 2017;Gardner et al, 1995;Lipoma et al, 2019), and also to identify changes in vegetation composition that were the result of factors different from exclusion, principally variation in precipitation (Supporting Information Appendix 1). High-rainfall periods in the ecosystem of the Chaco forest are supposed to have a synergistic effect with exclusion from grazing (Adamoli et al, 1990;Cabido et al, 1992Cabido et al, , 1994Cotroneo et al, 2018) and it has been suggested that the restoration of degraded arid ecosystems might be achieved in an efficient way by adjusting stocking rates to the occurrence of temporal windows of opportunity (Holmgren & Scheffer, 2001;Meserve et al, 2003).…”
Section: Testing Resilience Apart From Other Driverssupporting
confidence: 81%
“…Fresh litter (senescent leaves released from the tree) was collected in and around the plots over a period of one year, oven dried at 65℃ and stored. Litter of the two standard species, A. communis and J. ichu , was imported to Costa Rica from collection sites in Central Argentina (Cuchietti et al, ; Vaieretti et al, ).…”
Section: Methodsmentioning
confidence: 99%